Medical Malpractice in the United States of America: Lessons to Learn for Indonesia - Muh Endriyo Susila (Universitas Airlangga, 2021)
Many countries have established a system that serves the liability and settlement of medical malpractice disputes in response to rising medical malpractice claims against doctors. The medical malpractice system in the United States of America (USA) is relatively well developed compared to other countries. Besides the pretrial screening process in medical malpractice litigation, various alternatives to litigation have been developed in the USA. This paper aims to explore the development of the medical malpractice system in the USA and the lessons Indonesia can learn from it. This normative legal research relies on secondary data, particularly online sources. It found that Indonesia can adopt some initiatives in the USA to improve its medical malpractice system, especially the pretrial screening panel. The pretrial screening process is expected to eliminate frivolous claims and reduce unnecessary legal actions against doctors.